2013
DOI: 10.1186/1472-6882-13-326
|View full text |Cite
|
Sign up to set email alerts
|

Methanol extract of Melastoma malabathricum leaves exerted antioxidant and liver protective activity in rats

Abstract: BackgroundMelastoma malabathricum L. (Melastomaceae) is a small shrub with various medicinal uses. The present study was carried out to determine the hepatoprotective activity of methanol extract of M. malabathricum leaves (MEMM) against the paracetamol-induced liver toxicity in rats model.MethodsThe respective chemicals and herbal solutions (10% DMSO, 200 mg/kg silymarin or MEMM (50, 250 and 500 mg/kg)) were administered orally to rats once everyday for 7 days followed by the hepatotoxicity assay. The blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 47 publications
2
31
0
2
Order By: Relevance
“…For flavonoids, tannins, triterpene and steroids - + : weak colour; ++ : mild colour; +++ : strong colourFor saponins −+: 1 – 2 cm froth; ++: 2 – 3 cm froth; +++: > 3 cm frothFor alkaloids: − +: negligible amount of precipitate; ++: weak precipitate; +++: strong precipitate a Adapted from report made by Mamat et al [31]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For flavonoids, tannins, triterpene and steroids - + : weak colour; ++ : mild colour; +++ : strong colourFor saponins −+: 1 – 2 cm froth; ++: 2 – 3 cm froth; +++: > 3 cm frothFor alkaloids: − +: negligible amount of precipitate; ++: weak precipitate; +++: strong precipitate a Adapted from report made by Mamat et al [31]…”
Section: Resultsmentioning
confidence: 99%
“…The HPLC profile of MEMM has been published by Mamat et al [31]. The HPLC profile of the most effective fraction (PEMM) was established according to the same methods [31].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MECN is subjected to phytochemical tests for the presence of alkaloids, saponins, flavanoids, tannins, triterpenes and steroids according to the method described by Zakaria et al (2011b) and Mamat et al (2013).…”
Section: Phytochemical Screeningmentioning
confidence: 99%
“…flavonoids, triterpenes, tannins and saponins) (Surh, 2002;Zakaria et al, 2011). MEMM has demonstrated high antioxidant and free radical scavenging potential when assessed by the DPPH radical scavenging and superoxide scavenging assays suggesting these effects direct or indirect contribution to the extract's observed anti-carcinogenic activity (Li et al 2008 Interestingly, we have also detected quercitrin in the MEMM (Mamat et al, 2013), which have been earlier reported to exert in vitro anti-carcinogenic activity against mouse JB6 cells and antioxidant activities (Ding et al, 2010). Moreover, quercitrin down-regulates transactivation of AP-1 and NF-κB induced by UVB or TPA.…”
Section: Discussionmentioning
confidence: 59%